Cognitive engagement in a computer-supported collaborative learning environment - A. Shukor, Nurbiha (2012)
The quality of online learning is determined by students’ cognitive engagement. Recent research reported that students are cognitively engaged but mostly at the low-level of cognitive engagement (CE). High-level of CE is more beneficial as it shows that new knowledge is constructed. This research is proposing the usage of online computer-supported collaborative learning (CSCL) environment to promote students’ CE to the higher-level. Samples were undergraduate students from two different cohorts who enrolled in the Web-based Multimedia Development subject. Cohort I (n = 61) consists of students who involved in earlier investigation on students’ CE in online learning environment and cohort II (n = 20) consists of students who learned in CSCL environment. Through pre-experimental research design, students from cohort II answered the pre and post performance tests. Next, they were asked to solve CSCL tasks through online discussions in CSCL environment. Their online discussion scripts were collected and analyzed using content analysis method to obtain CE codes. The students’ server log files, CE codes and performance test score were gathered to structure a performance predictive model using WEKA data mining software. Findings show that 34.04% of students from cohort I contributions in online discussion were at the low level. As for students in cohort II, they shows 70.23% cognitive contributions in nature but the percentages of low-level CE remains higher than the high-level CE. However, the CSCL environment was found to provide positive impact on students’ performance in test (p < 0.05). Meta analysis (Cohen’s d = 1.858) of t-test shows that the effect size of CSCL environment towards students’ performance in test is significant. Even if this experiment is repeated, the power value (0.970) implies that the same result will be obtained. The performance predictive model predicts ‘argumentation’ as important for better performance in test. Conclusively, CE can be nurtured in CSCL environment but it is influenced by factors such as the group functions, the instructor’s role, and the type of CSCL task. For better future performance in test, this research suggests that students should be encouraged to provide more arguments on statements while solving CSCL tasks such as justifying statements and giving critics with elaboration.